Supplementary descriptions of Pergalumna amamiensis Aoki, 1984 (Acariformes, Galumnoidea) from Ryukyu Islands - Hagino, Wataru; Shimano, Satoshi (Zootaxa, 2019)
A species of oribatid mites, Pergalumna amamiensis was collected from Amami-Ohshima Island, Ishigaki Island, and Okinawa Island, Southwestern Japan. The specimens were studied in detail, and supplementary descriptions are provided; these include features of the rostrum, the subcapitulum and the surface pattern of pteromorphs. The main morphological traits for this species are summarized as follows; body length 519–570 μm, body width 363–410 μm, rostral tip pointed, sensillus with a long stalk covered by minute barbs, porose areas Aa bulbous, porose areas A1, A2, and A3 circular, surface of pteromorphs ornamented by fine granular structure and dense wrinkles, fine granular structure on prodorsum, subcapitulum, genital plates and anal plates, median pore on the notogaster represented as single pore.